Analysis and Design of Data Governance at the Financial Services Authority - Desta Arisandi; Tubagus Muhamad Yusuf Khudri (InFestasi, 2021)
This research is a case study conducted at the Financial Services Authority on the implementation of a data governance framework based on the model from The Data Management Association in 2017. The purpose of this study is to produce a data governance framework in managing integrated Financial Services Sector data. This study uses a qualitative approach in describing data governance activities. The research instruments were interviews, questionnaires, and content analysis. The results show that data governance frameworks provide guidelines for various parties to act in accordance with the strategies that have been developed. Data governance program at the Financial Services Authority requires further improvements in the form of establishing a data governance charter, assessing the maturity level of data management capabilities, defining the operational framework, adjusting the roadmap, establishing a change management team, creating mechanisms and procedures for handling data problems, and developing tools and techniques which supports the entire data governance program.